Innovativeness of the US economy. Permanent or weakening dominance?; Innowacyjnosćǵospodarki Stanoẃ Zjednoczonych. Trwała czy słabnaca dominacja? - Witold Kasperkiewicz; Wiesław Rogalski (Comparative Economic Research. Central and Eastern Europe, 2010)
The main purpose of the paper is to analyze the innovativeness of the US economy against those of European and Asian economies. The particular attention was given to the reasons for the forming of the US dominance in the field of innovation. The paper also considers the process of vanishing of American dominance at the end of 1990s. The paper is divided into three parts. In the first one, main causes of American leadership in the field of technology are explained. In the second part, innovation performance of the US economy in comparison with the EU and Asian economies is presented. Finally, there is an analysis of innovation capacity of US economy in the context of challenges resulting from the financial and economic crisis. – – Celem opracowania jest wyjasńienie zŕod́eł amerykanśkiej dominacji w dziedzinie innowacji, dokonanie oceny poziomu innowacyjnosći amerykanśkiej gospodarki na tle krajoẃ Unii Europejskiej, Azji, a takzė odpowiedzńa pytanie dotyczace perspektyw utrzymania przez te gospodarke pozycji lidera w wysćigu technologicznym. Strukture opracowania mozṅa przedstawicńastepujaco: po wprowadzeniu dokonano charakterystyki głoẃnych czynnikoẃ i procesoẃ, ktoŕe przyczyniły sie do powstania dominacji gospodarki Stanoẃ Zjednoczonych w dziedzinie innowacyjnosći, nastepnie poddano analizie zjawisko zmniejszania sie przewagi innowacyjnej tej gospodarki nad reszta sẃiata, a w dalszej kolejnosći skoncentrowano uwage na zagadnieniu wpływu wspoĺczesnego kryzysu gospodarczego na perspektywy utrzymania przewagi technologicznej Stanoẃ Zjednoczonych.
Keywords: 330